Misuse of emergency powers and its effect on civil society—the case of Hungary - Mészáros, Gábor (Frontiers in Political Science, 2024)
Democratic tolerance has been used for their own destruction in Hungary. Gradually, various forms of crisis management have become the very nature of the governing political parties since 2010. Under the framework of Carl Schmitt's enemy-friend dichotomy, the Orbán regime has created its own “enemies” partially among those who would never be thought to be a threat to a constitutional democracy but to be considered its foundational elements (political opposition, NGOs, free media, etc.). This article shows how emergency powers and autocratic legalism were misused against civil society. There is one simple goal for the Hungarian autocratic regime: defending “our democracy” against “them,” who would still like to promote liberal democracy and the rule of law.